2005
DOI: 10.1159/000088055
|View full text |Cite
|
Sign up to set email alerts
|

Liver Support Therapy: An Overview of the AMC-Bioartificial Liver Research

Abstract: Acute liver failure (ALF) is a disease with a mortality of 60–90% depending on the cause. Only high-urgency liver transplantation is able to increase survival compared to standard intensive care therapy. Liver transplantation is hampered by the increasing shortage of organ donors, resulting in a high incidence of patients with ALF dying on the transplantation waiting list. Amongst a variety of liver assist therapies, bioartificial liver (BAL) therapy is marked as the most promising solution to bridge ALF patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 74 publications
0
25
0
Order By: Relevance
“…Despite a highly promising start, using extracorporeal liver support systems revealed several serious problems, including quick loss of functional activity and limited ex vivo viability of primary hepatocytes [Xiong et al 2008]. The bioartificial liver device AMC, developed in the Academic Medical Center (Amsterdam) and based on pig hepatocytes, showed favorable results in a phase I clinical trial including the complete recovery of 1 patient and no need for further liver transplant [van de Kerkhove et al, 2005]. However, Fruhauf et al [2009] isolated endogenous reovirus from primary porcine hepatocytes used in the AMC machine capable of infecting cultured primary human hepatocytes.…”
Section: Extracorporeal Bioartificial Liver Support Systems (Bioartifmentioning
confidence: 99%
“…Despite a highly promising start, using extracorporeal liver support systems revealed several serious problems, including quick loss of functional activity and limited ex vivo viability of primary hepatocytes [Xiong et al 2008]. The bioartificial liver device AMC, developed in the Academic Medical Center (Amsterdam) and based on pig hepatocytes, showed favorable results in a phase I clinical trial including the complete recovery of 1 patient and no need for further liver transplant [van de Kerkhove et al, 2005]. However, Fruhauf et al [2009] isolated endogenous reovirus from primary porcine hepatocytes used in the AMC machine capable of infecting cultured primary human hepatocytes.…”
Section: Extracorporeal Bioartificial Liver Support Systems (Bioartifmentioning
confidence: 99%
“…151 With further optimization, dead space in the bioreactor was reduced so that the biofunction of liver cells was kept at 80%-90% of day 1 after 3 day cultivation. 152 In addition, Mareels et al 153 reported their application of rheological numerical model for the optimization the distribution of oxygen in the AMC bioreactor. However, it has yet reported the clinical studies with optimized bioreactor AMC.…”
Section: Amc-bioartificial Livermentioning
confidence: 99%
“…The possibilities of cellular transplantation have been discussed earlier in this review, and the main constraints remain to be difficulties in sourcing and maintaining viable hepatocytes. Attempts in immortalisation of primary hepatocytes are currently only partially successful as proliferation and hepatocellular function can appear mutually exclusive [41]. A recently developed human hepatoma cell line HepaRG [42] retains some attributes of primary hepatocytes but nonetheless remains a cancer cell line, and therefore is restricted in their application to in vitro modelling of human drug toxicity and incorporation in extracorporeal support devices.…”
Section: Modalities Of Liver Stem Cell Therapymentioning
confidence: 99%